Negative ions and their role in the development of science and technology - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Negative ions are formed in the process of the interaction between the electron with the integrated electric dipole moment and the induced electric dipole moment due to polarization. In the continual regime, at orbital velocity, the emission of negative ions from the surface of the heat-shielding coating leads to the formation of a double electric layer with a very dense plasma while at the escape velocity the same emission of negative ions creates an explosive character of burning of the heat-shielding coating. In the free molecular flow regime, the emission of negative ions results in intense violet-blue glow while high positive potentials are induced on the surface of an aircraft. In nanotechnologies, the ionization of negative ions determines the parameters of vacuum arc discharge. Negative ions participate in the formation of an electrostatic machine in the human body.